PENGARUH PEMBELAJARAN DARING TERHADAP MOTIVASI BELAJAR PKn PADA MASA PANDEMI COVID-19 DI SMP NEGERI 1 BUNGARAYA KABUPATEN SIAK - Nanang Tarmizi; Ahmad Eddison; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by the fact that during this pandemic, schools are required to carry out online learning, but we see on the news and on social media that many students feel bored and bored with online learning who do not know for sure how long students will carry out online learning and expectations. students can carry out face-to-face learning as usual again. Based on the background of the problem, the formulation of the problem is how is the influence of online learning on the motivation to learn Civics during the Covid-19 pandemic at SMP Negeri 1 Bungaraya. The purpose of this study was to determine the effect of online learning on Civics learning motivation during the Covid-19 pandemic at SMP Negeri 1 Bungaraya. In this study, the writer will present the data which is the result of the research that the author conducted at the research locationat namelySMP Negeri 1 Bungaraya,, where this study used observation and questionnaire data collection techniques. In this study, the authors took as many as 35 students as respondents to fill out the author's research questionnaire. The results of this study were analyzed using descriptive statistical analysis methods. Descriptive statistics are statistics used to analyze data by describing or describing the data that has been collected as it is without intending to make conclusions that apply to the public or generalizations. Based on the results of research conducted, that online learning during this pandemic affects the learning motivation of class VIII students at SMPN 1 Bungaraya. This is because the highest frequency results are at very high intervals, with a percentage of 81.4% which has been analyzed using SPSS Statistics 17.0.Key Words: Influence, Civics Learning Motivation, Online Learning